Kebijakan Pemerintah Mengenai Coronavirus Disease (COVID-19) di Setiap Provinsi di Indonesia Berdasarkan Analisis Klaster - Glisina Dwinoor Rembulan; Tony Wijaya; Desribeth Palullungan; Kartika Nur Alfina; Muhammad Qurthuby (JIEMS (Journal of Industrial Engineering and Management Systems), 2020)
Coronavirus disease (COVID-19) is a disease that was only discovered in 2019 and has been reported to have spread to almost all over the world. This pandemic has caused anxiety and fear for all Indonesians because it can be transmitted easily through humans. This study aims to cluster each province in Indonesia into certain clusters so that they can find out the characteristics, movements, and government policies that must be carried out in each cluster. This study uses secondary data regarding COVID-19 cases in Indonesia, which reached 4800 data from March 1 to August 11, 2020, in 34 Indonesian provinces. The four variables used were the number of cases of death, the number of cured cases, the number of active cases, and the number of deaths per one million population. Cluster 1 has a high risk because it has the highest variable number of active cases and the number of deaths per one million population. Cluster 2 has a low risk because it has a variable with the highest number of cured cases and the lowest number of active cases. Cluster 3 has a moderate risk because it has the lowest number of cures variable and the moderate number of active cases. The government policy in cluster 1 should prioritize the variable number of active cases and the number of death cases per one million population, cluster 2 must prioritize the variable number of deaths, and cluster 3 must prioritize the variable number of active cases.